Experimental Investigation of a Thermochemical Reactor for High-Temperature Heat Storage via Carbonation-Calcination Based Cycles - Wild, Michael; Lüönd, Lorenz; Steinfeld, Aldo (Frontiers in Energy Research, 2021)
We report on the design of a modular, high-temperature thermochemical energy storage system based on endothermic-exothermic reversible gas-solid reactions. It consists of an array of tubular reactors, each containing an annular packed bed subjected to radial flow, and integrated in series with a thermocline-based sensible thermal energy storage. The calcination-carbonation of limestone, CaCO3 <-> CaO + CO2, is selected as the reversible thermochemical reaction for the experimental demonstration. Synthetized 4.2 mm-mean size agglomerates and 2 mm-mean size granules of CaO with 42%wt sintering-inhibitor MgO support attained reaction extents of up to 84.0% for agglomerates and 31.9% for granules, and good cycling stability in pressure-swing and temperature-swing thermogravimetric runs. A lab-scale reactor prototype is fabricated and tested with both formulations for 80 consecutive carbonation-calcination cycles at ambient pressure using a temperature-swing mode between 830°C and 930°C. The reactor exhibited stable cyclic operation and low pressure drop, and yielded specific gravimetric and volumetric heat storage capacities of 866 kJ/kg and 322 MJ/m3 for agglomerates, respectively, and 450 kJ/kg and 134 MJ/m3 for granules, respectively.